2012
DOI: 10.1108/17581181211230603
|View full text |Cite
|
Sign up to set email alerts
|

The rise of contingent faculty: its impact on the professoriate and higher education

Abstract: Purpose -The faculty, as higher education's most valuable asset, is being dramatically altered. Changes in appointment status drive this alteration, resulting in the essential work of faculty being transformed. Given this change in faculty composition, this study seeks to examine how faculty appointments relate to the production of faculty work in teaching, research, and service. Faculty appointments affect faculty work and it implies that the function of higher education also is altered. The purpose of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…An equally important implication is the simple fact that, as this sample demonstrated, NTT faculty can attain well-being in their positions. This goes against the characterizations provided by some scholars (e.g., Bowden & Gonzalez, 2012) of NTT faculty as lacking satisfaction and commitment to their institutions and is consonant with previous findings (e.g., Antony & Hayden, 2011) that NTT faculty generally display overall satisfaction at similar levels to their T/TE peers.…”
Section: Discussionsupporting
confidence: 78%
“…An equally important implication is the simple fact that, as this sample demonstrated, NTT faculty can attain well-being in their positions. This goes against the characterizations provided by some scholars (e.g., Bowden & Gonzalez, 2012) of NTT faculty as lacking satisfaction and commitment to their institutions and is consonant with previous findings (e.g., Antony & Hayden, 2011) that NTT faculty generally display overall satisfaction at similar levels to their T/TE peers.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, those who have followed alternative career trajectories or who are not in traditional tenure-track positions, increasingly find themselves positioned as outsiders within their institutions and/or the broader academic community. These academics may find that traditional organizational structures and processes fail to offer them professional support for their academic career progressions with respect to teaching, research, and/or administrative service (Anderson, 2007;Bowden & Gonzalez, 2012;Nicol, 2000). Therefore, academics in these positions may be unable to access resources, engage with other faculty members, participate in research projects, or access research opportunities that other academics within the institution are able to access.…”
Section: Introductionmentioning
confidence: 92%
“…Scholars have expressed concerns about the impact of adjuncts on the quality of teaching and student learning outcomes (AAUP, 2010;Benjamin, 2002Benjamin, , 2003Hagedorn et al, 2002;Schibik & Harrington, 2004). Others have warned that excessive adjunct reliance is a threat to academic quality and risks the integrity of higher education (Bowden & Gonzalez, 2012;Kezar & Maxey, 2016b;Maxey & Kezar, 2015). Adjunct teaching effectiveness has been measured by student course evaluations and rates of student persistence, transfer, and graduation.…”
Section: Teaching Effectivenessmentioning
confidence: 99%
“…Adjuncts typically invested less time in course preparation, were less available to students, and were more likely to rely on lecture over learner-centered teaching methods (CCCSE, 2014). Bowden and Gonzalez (2012) revealed that adjuncts were more likely to rely on standardized testing than on assignments requiring writing and critical thinking and less likely to utilize student presentations and group work in class. CCCSE (2014) observed that adjuncts were less likely to rely on highly-impact educational practices than full-timers.…”
Section: Adjunct Teaching Practicesmentioning
confidence: 99%
See 1 more Smart Citation